Nickel-based anode with water storage capability to mediate carbon deposition for direct ethanol solid oxide fuel cells - Wang, W.; Su, Chao; Ran, R.; Zhao, B.; Shao, Zongping; Tade, Moses; Liu, Shaomin (Wiley-VCH Verlag GmbH, 2014)
The potential to use ethanol as a fuel places solid oxide fuel cells (SOFCs) as a sustainable technology for clean energy delivery because of the renewable features of ethanol versus hydrogen. In this work, we developed a new class of anode catalyst exemplified by Ni+BaZr0.4Ce0.4Y0.2O3 (Ni+BZCY) with a water storage capability to overcome the persistent problem of carbon deposition. Ni+BZCY performed very well in catalytic efficiency, water storage capability and coking resistance tests. A stable and high power output was well maintained with a peak power density of 750 mW cm−2 at 750 °C. The SOFC with the new robust anode performed for seven days without any sign of performance decay, whereas SOFCs with conventional anodes failed in less than 2 h because of significant carbon deposition. Our findings indicate the potential applications of these water storage cermets as catalysts in hydrocarbon reforming and as anodes for SOFCs that operate directly on hydrocarbons.